A model to predict changes in resilient modulus resulting from wetting and drying - Perez Garcia, Natalia (2025)
The resilient modulus of a soil is an important parameter needed for pavement design. However, this parameter experiences post-compaction seasonal changes during the service life of the pavement as a result of wetting or drying of the soil during dry or rainy periods. Variations in the resilient modulus should be introduced into pavement design methodologies. Research literature shows resilient modulus results from other countries; however, the information is scarce for Mexican soils. In this paper, the authors show results of a research carried out in the laboratory to evaluate a model for the prediction of the effect of wetting and drying on the resilient modulus of soils classified as clays, silt, and sand. Several samples were prepared at optimum conditions using the Proctor standard test. Some specimens were then dried by allowing a loss of water through evaporation while others were allowed to gain water through capillarity (assumed to simulate post-compaction conditions). After the samples were conditioned to new water contents, resilient modulus tests were performed following the NCHRP 1-28A protocol. The results show that the resilient modulus can be predicted using a model which is a function of the deviator stress and confining pressure (i.e., (sd/s3) and the variation of water content from optimum water content conditions (i.e., the condition after field compaction). The R2 results when using the proposed resilient modulus model was 84.1%.